Molecular characterization of Spanish Prunus avium plus trees - Fernandez-Cruz, Javier; Fernandez-Lopez, Josefa; Miranda-Fontaiña, Maria Eugenia; Diaz, Raquel; Toval, Gabriel (Forest Systems, 2014)
Aim of the study: The Breeding Program of wild cherry (Prunus avium) developed by Lourizán Forest Research Center (NW Spain), aims for the creation of the Main Breeding Population, that is formed by a large number of plus trees and for obtaining an Elite Population generated from controlled crosses of a number of plus trees selected by, at least, one trait of economic importance. The aim of this study was to genotype 131 accessions of Prunus avium plus trees, included in the breeding program.Area of study: The Prunus avium plus trees are located in the North, Northwest and Central Spain.Material and Methods: The Prunus avium plus trees were genotyped with nine microsatellites. Several genetic parameters were calculated. Genetic data were analyzed with STRUCTURE and the genetic distance between the plus trees were calculated.Main results: A total of 122 multilocus genotypes were detected. Several accessions with the same genotype were identified, which could be due to clonality or to labelling errors. The nine microsatellites are useful for identifying individuals because the combined probability of identity was low (PI = 5.19X10-9). Bayesian methods detected two genetic clusters in the sampled plus trees.Research highlights: The unique genotypes identified in this work are suitable for being included in the elite breeding population for economic traits.Keywords: Prunus avium; breeding program; microsatellite; genetic distance.